A proposition of mobile fractal image decompression - Nikiel, Sławomir (Zielona Góra: Uniwersytet Zielonogórski)
Multimedia are becoming one of the most important elements of the user interface with regard to the acceptance of modern mobile devices. The multimodal content that is delivered and available for a wide range of mobile telephony terminals is indispensable to bind users to a system and its services. Currently available mobile devices are equipped with multimedia capabilities and decent processing power and storage area. The most crucial factors are then the bandwidth and costs of media transfer.
Keywords: fractals; image processing; fractal image compression; mobile media; texture mapping